Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - 9 (My University, 2020)
Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice
Keywords: WRKY transcription factor; Chiều cao cây lúa; Kích thước hạt